Redefining chemotherapy-induced peripheral neuropathy through symptom cluster analysis and patient-reported outcome data over time - Wang, Mian; Cheng, Hui Lin; Lopez, Violeta; Sundar, Raghav; Yorke, Janelle; Molassiotis, Alex (BMC cancer, 2019)
Background Chemotherapy-induced peripheral neuropathy (CIPN) is common among cancer patients treated with neurotoxic chemotherapy agents. Better knowledge on symptom clusters of CIPN may help improve symptom management in clinical practice. This study aimed to identify symptom clusters of CIPN and to map their trajectories before initiation of chemotherapy to 12-month follow-up. Methods A secondary analysis of a longitudinal dataset was conducted using principal component approach. The European Organization for the Research and Treatment of Cancer Quality of Life Questionnaires Core 30 and CIPN 20 were used to measure symptom clusters of CIPN in patients with mixed cancer diagnosis across 10 time points over 12 months. Results Sample size in each assessment point ranged from 118 to 343 participants. Four CIPN symptom clusters were identified, including a clear sensory neuropathy symptom cluster, a mixed motor-sensory neuropathy symptom cluster, a mixed sensorimotor neuropathy symptom cluster, and a less clear autonomic neuropathy symptom cluster. The core symptoms in each symptom cluster were mostly stable while the secondary symptoms changed over time. Conclusions The analysis suggests that CIPN is predominantly a sensory neuropathy with no evidence of a pure motor dysfunction but with mixed motor-related and autonomic changes accompanying sensory dysfunctions over time. Future symptom management strategies can be designed based on the morphology of CIPN.